Combined analyses of the antiproton production from cosmic-ray interactions and its possible dark matter origin - De La Torre Luque, Pedro (Journal of cosmology and astroparticle physics, 2021)
Recent cosmic-ray (CR) studies have claimed the possibility of an excess on the antiproton flux over the predicted models at around 10 GeV, which can be the signature of dark matter annihilating into hadronic final states that subsequently form antiprotons. However, this excess is subject to many uncertainties related to the evaluation of the antiproton spectrum produced from spallation interactions of CRs. In this work, we implement a combined Markov-Chain Monte Carlo analysis of the secondary ratios of B, Be and Li and the antiproton-to-proton ratio ( p ̅/ p ), while also including nuisance parameters to consider the uncertainties related to the spallation cross sections. This study allows us to constrain the Galactic halo height and the rest of propagation parameters, evaluate the impact of cross sections uncertainties in the determination of the antiproton spectrum and test the origin of the excess of antiprotons. In this way, we provide a set of propagation parameters and scale factors for renormalizing the cross sections parametrizations that allow us to reproduce all the ratios of B, Be, Li and p ̅ simultaneously. We show that the energy dependence of the p ̅/ p ratio is compatible with a pure secondary origin. In particular, we find that the energy dependence of the evaluated p ̅/ p spectrum matches that observed from AMS-02 data at energies above ∼3 GeV, although there is still a constant ∼10% excess of p ̅ over our prediction. We discuss that this discrepancy is more likely explained from a ∼10% scaling in the cross sections of antiproton production, rather than a component of dark matter leading to antiprotons. In particular, we find that the best-fit WIMP mass (∼300 GeV) needed to explain the discrepancy lies above the constraints from most indirect searches of dark matter and the resultant fit is poorer than with a cross sections scaling.